2022
DOI: 10.3389/fphar.2022.819327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Finerenone in Chronic Kidney Disease: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Background: Chronic kidney disease (CKD) is a global public health issue. In recent years, the effectiveness of finerenone for treatment of CKD has been the subject of considerable debate. The main objective of the current meta-analysis was to validate the clinical efficacy and safety of finerenone in patients with CKD.Methods: Seven databases were searched for randomized controlled trials (RCTs) comparing finerenone with placebo in patients with CKD. Data from eligible studies were extracted, and the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Although in most of genetic nephropathy the only therapeutic option is non-specific pharmacological proteinuria lowering with blockers of the renin-angiotensin-aldosterone system [ 26 ] or, more recently, with sodium-glucose cotransporter 2 inhibitors (SGLT2i) [ 27 ]. The association of CyA to the traditional anti-proteinuric therapy may represent an alternative option for patients with MAFB -associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although in most of genetic nephropathy the only therapeutic option is non-specific pharmacological proteinuria lowering with blockers of the renin-angiotensin-aldosterone system [ 26 ] or, more recently, with sodium-glucose cotransporter 2 inhibitors (SGLT2i) [ 27 ]. The association of CyA to the traditional anti-proteinuric therapy may represent an alternative option for patients with MAFB -associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The phase II program ARTS (MinerAlocorticoid Receptor antagonist Tolerability Study) was conducted in CKD patients with chronic heart failure and reduced ejection fraction (HFrEF), with spirololactone as a comparator (12). There was a comparable reduction in pro-brain natriuretic peptide (NT-Pro BNP) as well as UACR, with less gynaecomastia and hyperkalaemia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The FIRAGO-DKD study was the first to show a positive cardiovascular result using a 4-point MACE (composite of death from cardiovascular causes, nonfatal myocardial infarction, nonfatal stroke, or hospitalization for heart failure) in T2D patients with established CKD (18). A meta-analysis of five RCTs by Zhang et al using the fixed effects model demonstrated a significant improvement in UACR as well as retardation of eGFR decline with finerenone compared to placebo (12). However, another meta-analysis by Fu et al with four studies using the fixed effects model demonstrated a positive impact of finerenone on UACR reduction but not on the retardation of eGFR decline (13).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) There were a couple of meta-analyses estimating the effectiveness of nerenone versus placebo on the renal composite as well as the individual components of urine albumin creatinine ratio (UACR) and estimated glomerular ltration rates (eGFR). (13,14) Although both meta-analyses documented similar bene ts regarding renal composite, there was discordance as far as bene ts on eGFR reduction were concerned. Moreover, of the ve included citations, one by Pitt el al did not include patients with T2D, while the other four did.…”
Section: Introductionmentioning
confidence: 99%